The Effect of Interactive Social Media Marketing and Online Consumer Reviews on Digital Trust and Interest in Using e-Wallets in Indonesia - Gunawan, Arif; Yusendra, M. Ariza Eka (Prosiding International conference on Information Technology and Business (ICITB), 2023)
The purpose of this study is to explore the interest in using e-Wallets in Indonesia. Researchers hypothesize that the high use of e-Wallets in Indonesia is due to high digital trust so that users feel close and believe that e-Wallets are a solution to facilitate their transactions. This digital trust is hypothesized by researchers to mostly come from aggressive interactive social media marketing from vendors and the influence of online consumer reviews of netizens who report a lot of information related to the use of e-wallets. This type of research is explanatory research, with a population of e-Wallet users in Indonesia and a sample of 100 respondents. The analytical tool used is SEM-PLS to be able to measure complex causal relationships between the variables studied.Keywords-digital marketing, e-Wallet, Social media marketing, Online review